Pelatihan Deteksi Dan Stimulasi Tumbuh Kembang Psikososial Anak Pra Sekolah Di TK ABA 30 - Zahid Fikri; Muhammad Ari Arfiyanto; Oktika Khoirunnisa; Fridha Luciana Andini (Pelita Abdi Masyarakat, 2021)
Background: Development is a process of psychological change as a result of the maturation of a child's psychological and physical functions. Stimulation of growth and development in children under five is an activity to stimulate the basic abilities of children so that children grow and develop optimally. Lack of stimulation can cause developmental irregularities in children. The purpose of this service is to improve the ability and understanding of the child's parents in detecting and stimulating the psychosocial development of pre-school children at TK ABA 30. Method: This service uses a learning method that begins with discussion and pre-test the ability of participants, discussion, training, and post. test. Participants in the service were parents of 20 students. Result: Result : The result of this service was an increase in the knowledge and understanding of the parents of students in early detection of psychosocial development. Conclusion: There is an increase in the knowledge level score of the parents of TK ABA 30 Malang students before the service and after the service, there are 2 stimulations that can be carried out well, namely doing homework and eating with family, and there is 1 thing that parents are less able to do in stimulating the psychosocial development of children is playing a role.